LEGAL PROTECTION OF FAMOUS BRANDS BASED ON LAW NUMBER 20 OF 2016 CONCERNING BRANDS AND GEOGRAPHICAL INDICATIONS - Donny Agus Prakoso; Jeane neltje sally (Warmadewa Press, 2024)
Brand protection (including well-known brands) in Indonesia is regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications replacing the previous regulation, namely Law Number 15 of 2001 concerning Marks. Even though there are already regulations in place, brand disputes in Indonesia still often occur, especially similarities in essence. The title adopted by the author in writing this thesis is